UCAmI 2018 2018
DOI: 10.3390/proceedings2191255
|View full text |Cite
|
Sign up to set email alerts
|

Beacon-Based Fuzzy Indoor Tracking at Airports

Abstract: An application of Bluetooth beacons is here proposed to perform real-time tracking of the locations and movements of airport staff through different monitored airport infrastructure elements, such as rooms, terminals or boarding gates. With respect to this, the aim is to provide an efficient location service of airport workers and users through an indoor tracking controller based on fuzzy logic. For this purpose, a mobile application and a Web service have been implemented. This location knowledge may be decis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The study findings also confirmed that i-Beacons enables the customer to interact directly with the provided tourism services, helps attract attention to unknown places and facilitates the visit by domestics and international tourists, helps cover any shortage of information and rare languages, contributes to creating new job opportunities in the field of information technology, gives tourism businesses the opportunity to provide the services and information needed by tourists in various languages, supports the tour guide in many languages and supports humans who can easily forget and leads to easy access to service and improvement of the tourism experience. The previous advantages come in line with Singh et al (2015), Toledo et al (2018), and Ferreira et al (2020. who confirmed that i-Beacons is considered one of smart marketing techniques offers a number of benefits including enhancing flexibility, good tourist experience, and suitability to complex intermodal transport networks, as well, giving tourist more details about the destination and gives him the opportunity to discover new destinations.…”
mentioning
confidence: 65%
“…The study findings also confirmed that i-Beacons enables the customer to interact directly with the provided tourism services, helps attract attention to unknown places and facilitates the visit by domestics and international tourists, helps cover any shortage of information and rare languages, contributes to creating new job opportunities in the field of information technology, gives tourism businesses the opportunity to provide the services and information needed by tourists in various languages, supports the tour guide in many languages and supports humans who can easily forget and leads to easy access to service and improvement of the tourism experience. The previous advantages come in line with Singh et al (2015), Toledo et al (2018), and Ferreira et al (2020. who confirmed that i-Beacons is considered one of smart marketing techniques offers a number of benefits including enhancing flexibility, good tourist experience, and suitability to complex intermodal transport networks, as well, giving tourist more details about the destination and gives him the opportunity to discover new destinations.…”
mentioning
confidence: 65%
“…Many systems have been developed that aim to estimate the location or activity of people during their everyday lives using sensors. Most common approaches are using GPS [ 5 ], Wi-Fi [ 7 , 23 , 24 ], cameras using computer vision [ 8 ], Bluetooth/BLE [ 9 , 10 , 11 ], ultra wide band (UWB) [ 25 ] and accelerometer sensors via dead reckoning [ 26 ] ( Table 4 ). GPS is efficient in outdoor location estimation, but not effective indoors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the outdoor environment, GPS can be used to identify time spent in “social places” [ 5 ] and Bluetooth can be used to infer the physical proximity of people [ 6 ]. In the home environment, sociability may be characterized using Wi-Fi [ 7 ], cameras using computer vision [ 8 ], Bluetooth [ 9 , 10 , 11 ], or combinations of multiple sensors such as RFID and cameras [ 12 ]. Each technology comes with different challenges.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations